Copyright Protection in the Digital Age: Addressing Challenges and Finding Solutions in Indonesian Civil Law - Sanusi, Rahmatinnisa Zahra; Sasea, Enny Martha; Bonsapia, Max (Sinergi International Journal of Law, 2024)
This research aims to identify the challenges faced in enforcing such legal protection. In the current digital era, advances in information and communication technology have had a major impact on various aspects of life including the creation and dissemination of intellectual works, which opens up opportunities for copyright infringement. This research uses a normative juridical approach with a qualitative descriptive analysis method. Data is collected through literature study and analysis of laws and regulations related to copyright protection and intellectual property rights. Primary data based on Law Number 28 of 2014 on Copyright, and secondary data collected from previous related research journals and other official documents. The research found that the legal protection of copyright and intellectual property rights in the digital era in Indonesia still faces various challenges. These challenges include the speed and volume of digital content dissemination, anonymity and global jurisdiction, and the effectiveness of Digital Rights Management (DRM) technology. Although Law No. 28/2014 on Copyright has regulated the economic and moral rights of creators, law enforcement is still ineffective. To overcome these challenges, a comprehensive and collaborative approach is needed between the government, digital platforms, copyright owners, and the public. Some of the proposed solutions include improved automatic detection technology using artificial intelligence (AI) and machine learning, harmonization of international copyright law, DRM technology reform, simplification and transparency of the copyright infringement reporting process, and increased public awareness and education regarding the importance of copyright and intellectual property rights.